PARALLEL FRAMEWORK OF MUá¸¤AMMAD AND MOSES'S STORY: AN ANALYSIS OF THE NARRATIVES OF á¸¤ALÄªMAH AL-SAÊ¿DIYYAH - Azmi, Ahmad Sanusi (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2018)
Kajian modern tentang asal-usul s?rah Nabawiyah telah menelusuri dan menemukan keberadaan pengaruh kitab suci sebelumnya dan unsur-unsurnya dalam narasi s?rah. Kisah tentang Halimah, sang ibu susuan, menurut Raven, menunjukkan kejadian paralel dengan kematangan Yesus ketika bayi, dalam Injil. Selain itu, para sarjana Muslim seperti Ibn Hisham ditemukan konsisten dalam membuat perbandingan paralel antara Muhammad dan Musa dalam karyanya. Tulisan ini memfokuskan pada kehidupan awal yang terfokus pada periode ?al?mah al-Sa'diyyah dengan menganalisis penggunaan referensi Al-Quran dalam narasi. Penelitian ini bersifat kualitatif dengan metode pendekatan kritis dan analisis tekstual untuk membaca cerita. Kajian ini menemukan proposisi bahwa ada dua kemungkinan alasan yang mengarahkan Ibn Hisham menambahkan ayat 28:12 dari Al-Qur'an sebagai referensi atas catatan waktu Muhammad sebagai bayi yang menyusu. Isu pertama ketidakjelasan digital dalam narasi Ibn Is?q. Dan yang kedua adalah memberikan kepercayaan kepada kisah kedua nabi, Muhammad dan Musa.Modern studies of the origin of s?rah nabawiyyah have traced and suggested the existence of influence of previous scriptures and their elements within the s?rah narrative. The extraordinary speed and marks of physical maturity in Prophet Mu?ammad?s wet-nurse period with Halimah, which, according to Raven, indicates a parallel occurrence with Jesus' precocity in the Gospels of the Infancy. Besides, Muslim scholars such as Ibn Hish?m was found to consistently make parallel comparison between Mu?ammad and Moses in his work. This study aims to explore the narratives of Prophet Mu?ammad?s early life, with special focus to his period with ?al?mah al-Sa?diyyah and analyse the use of Quranic reference in the narrative. The study is qualitative in nature in which the researcher employed critical and textual analysis to examine the story. The present study in its finding proposes that there are two possible reasons which lead Ibn Hish?m to adduce verse 28:12 of the Quran as his reference to the account of Mu?ammad?s time as a suckling infant. The first is to elucidate lexical obscurity in the narration of Ibn Is??q. And the second is to give credence to the similarity between the accounts of two prophets, Mu?ammad and Moses.